Climate change and the people's health - Friel, Sharon (New York Oxford University Press, 2019)
"Climate Change and the People's Health" offers a brave and ambitious new framework for understanding how our planet's two greatest existential threats comingle, complement, and amplify one another -- and what can be done to mitigate future harm. With insights from physical science, social science, and the humanities, this short book examines how climate change and social inequity are indelibly linked, and considering them together can bring about effective change in social equity, health, and the environment. -- From publisher's description.
Climate change, global justice, and health inequities -- It's a consumptagenic world : producing climate change, exacerbating health inequities -- Challenges and future prospects.
Includes bibliographical references and index.
Keywords: Climate Change; Population Health; Health Status Disparities; Social Determinants of Health